Knowledge of, Attitudes toward, Barriers to, and Uptake Rate of Influenza Virus Vaccine among Adults Aged ≥65 Years in Jordan: A Multicenter Cross-Sectional Study - Abu-Helalah M; Al-Hanaktah M; Almadani M; Asfour A; Batarseh FE; Abdelhadi NN; Al Odat BA; Sharkas SG; Alhashaika Jnr AI (Risk Management and Healthcare Policy)
Munir Abu-Helalah,1,2 Mohammad Al-Hanaktah,3 Mary Almadani,4 Amro Asfour,3 Fadi Essam Batarseh,5 Nadine N Abdelhadi,6 Baraa Ayed Al Odat,7 Satani G Sharkas,8 Alaa Ibraheem Alhashaika Jnr9 1Department of Family and Community Medicine, Faculty of Medicine, University of Jordan, Amman, 11942, Jordan; 2Public Health Institute, University of Jordan, Amman, 11942, Jordan; 3Faculty of Medicine, University of Jordan, Amman, 11942, Jordan; 4Jordan Hospital, Amman, 11152, Jordan; 5Ministry of Health, Amman, 11931, Jordan; 6Department of Clinical Pharmacy and Pharmacy Practice, Aqaba University of Technology, Aqaba, 11191, Jordan; 7Internal Medicine Department, Jordan University Hospital, Amman, 11942, Jordan; 8Internal Medicine Department, St. Elizabeth’s Medical Center, Boston, MA, 02118, USA; 9Specialty Hospital, Amman, 11193, JordanCorrespondence: Munir Abu-Helalah, Email m.abu-helalah@ju.edu.joPurpose: Seasonal influenza significantly impacts global health, especially among high-risk groups such as the elderly. People aged ≥ 65 years have the highest morbidity and mortality due to influenza infections. Despite international recommendations, influenza vaccine-uptake rates remain low in many regions worldwide. In Jordan, data on influenza vaccine uptake in people aged ≥ 65 years is lacking. This study aimed to assess vaccination rates, knowledge, attitudes, and barriers among the elderly in Jordan.Methods: This national cross-sectional study included 455 adults aged ≥ 65 years living at representative sites in Jordan in Amman, Irbid, Zarqa, and Karak. The study questionnaire was based on the health belief model and included data on demographics, influenza vaccination history, and knowledge of, attitudes toward, perceptions of, and barriers to influenza vaccine uptake.Results: Only 11.4% of participants received the influenza vaccine in the 2022– 2023 season, while 30.1% had ever been vaccinated. Rural residents, higher-income groups, and those insured by private institutions demonstrated higher vaccination rates of 14% and 15.4%, respectively (P< 0.05). Barriers to being vaccinated included perceived low susceptibility (43.7%), concerns about adverse effects (52.7%), and lack of social network recommendations (38.9%). Positive predictors included trust in vaccination guidelines, higher perceived risk, and health-care provider advice (P< 0.001).Conclusion: Influenza vaccination rates among older adults in Jordan are low compared to regional and international data. Interventions tailored to address barriers are needed to improve awareness, accessibility, and trust to reduce influenza-related morbidity and mortality.Keywords: influenza vaccines, elderly, above 65, uptake, barriers, attitudes, Jordan